The influence of the use of the more prevalent technology on the wages of older employees in Germany - Weller, Sabrina Inez [Verfasser] (My University, 2013)
"The labor market of tomorrow will be determined by the transition from an industrial to a knowledge society. In this process, the accumulation of human capital becomes increasingly important whilst opportunities for low qualified staff steadily diminish. Globalization and technological advancement results in enhanced economic participation of highly qualified staff in the form of higher wages and better employment opportunities. In the literature, this is attributed to the 'Skill-Biased Technological Change' (SBTC) (Nikutowski, 2007). According to the 'task approach' (Autor et al. 2003), the technological change due to falling computer prices (computerization) leads to changes in task structures which favor a trend towards routinization ('routinization hypothesis'). Alongside these developments Germany faces the challenge of demographic change, which is reflected primarily in the shrinking and ageing of the population (Siegrist et al. 2005). Consequently, Germany anticipates a distinct decline in the number of economically active persons in the next few decades (Federal Statistical Office, 2009). With the objective of securing adequate labor force potential the pension age was raised to 67 years, although statistics confirm that the average retirement age in Germany is a long way off the present age limit of 65 years (German Statutory Pension Insurance, 2012; Stößel, 2008). From this starting point, the question derived concerns the influence of technological change on occupational success, as measured by the gross wages of older working persons. The study examines whether the increasing use of computers in workplaces is leading to a shift towards non-routine tasks among older workers to the same extent as younger workers in accordance with the routinization hypothesis. Moreover, it is analyzed if among older workers it is also primarily the highly qualified persons who benefit from this trend in the form of higher gross wages. The analyses are based on data from the BIBB/IAB and BIBB/BAuA Employment Survey from the years 1979 to 2012, which enable the precise measurement of task profiles over time (Tiemann and Zopf, 2010). The work tasks carried out by older employees (aged 50-65) are investigated on the basis of the 'task approach' model (Autor et al. 2003)." (Authors' abstract, BIBB-Doku)
Keywords: P 1.8 Ältere; G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; G 1.2.2.1 Lohn- & Tarifsysteme; Älterer Arbeitnehmer; Technischer Wandel; Qualifikationswandel; Qualifikationsniveau; Tätigkeitsfelder; Lohnentwicklung; Multivariate Analyse